Response of common bean (Phaseolus vulgaris L.) Quivicán variety to the application of homeopathic medicines - García-Bernal, Milagro; Ojeda-Silvera, Carlos Michel; Batista-Sánchez, Daulemys; Abasolo-Pacheco, Fernando; Mazón-Suástegui, José Manuel (REVISTA TERRA LATINOAMERICANA, 2020)
The response of Phaseolus vulgaris L. variety Quivican to the application of homeopathic medicines as growth promoters was assessed during its initial plant development. A completely randomized experimental design was applied with three homeopathic treatments: TH1 [MgM-31CH (Magnesium metallicum 31 CH)], TH2 [MaMnP-3CH (Magnesium-Manganum phosphoricum)], TH3 [TH1 + TH2), and distilled water as Control group. The analyses showed the best results in the plants that received TH3 with a significant increase (P ≤ 0.05) with respect to the control group in the following response variables: length of stem (47.14%) and root (30.27%); biomass of fresh root (13.57%), leaves (68.36%) and stem (11.88%); dry biomass of leaves (84.72%) and stem (36.11%); leaf area (21.74%), stem diameter (39.54%) and number of leaves (16.66%). These results confirm that agricultural homeopathy is an eco-friendly and technologically viable alternative for bean cultivation because it stimulates growth, which allows obtaining more vigorous plants with greater productive potential and less dependent on agrochemicals. Because homeopathic medicines are harmless, the balance of the agroecosystem is also improved, achieving a positive impact in the short, medium and long term besides their application in conventional and organic agricultural production.